Hubungan Sikap Ibu Hamil Terhadap Hyperemesis Gravidarum Tingkat Sedang Di Ruang Kasuari RSU Anutapura Palu - Wayan Wirawan; Putu Suriyani (Jurnal Sains dan Kesehatan, 2017)
Pregnancy is a natural and physiological process. Any woman who has a healthy reproductive organs, Any woman who is pregnant will definitely experience Hyperemesis gravidarum mild, moderate or fallow. The purpose of this study is to determine the relationship Attitudes Against Hyperemesis gravidarum Pregnancy Rate Medium In Space cassowary RSU Anutapura Palu. The research in this study is a correlational study with descriptive analysis with cross sectional approach. The population in this study were all women with hyperemesis gravidarum in the room cassowary RSU Anutapura hammer, totaling 45 mothers with hyperemesis gravidarum. In this study using the analysis of univariate and bivariate significance invitation 0005 with 95% confidence level continued to Chi Square test and simple regression which is used to examine the relationship maternal attitude towards Hyperemesis gravidarum moderate In Space cassowary RSU Anutapura Palu. And how much influence the attitude of Pregnant Women Against Hyperemesis Gravidarum Medium Level. Of the 31 respondents based test using bivariate analysis showed signivikansi value 0.000 <0.05 which means there signivikan correlation between the two variables and chi square test with 31 respondents diproleh signivikansinya value of 0.00 <0.05, which means that the statistics there is a relationship between attitudes towards pregnant women with hyperemesis gravidarum moderate level, followed by a simple regression obtained F value hitung48,809 with a significance level of 0.000 <0.05, which means it has the effect of maternal attitudes towards hyperemesis grafidarum. In the results of the analysis show that there is a relationship attitude towards Hyperemesis gravidarum pregnant women being perceived level of pregnant mothers In Space cassowary RSU Anutapura Palu influence the level of 12.033%